Faktor Pendorong Komitmen Nasabah dalam Pengembalian Dana Pembiayaan di BMT UGT Sidogiri - Rozi, A. Fahrur; Amalia, Fika; Muhammad, Helmi (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2022)
This research is motivated by the instability of customer commitment in returning financing funds at BMT UGT Sidogiri Pagak Sub-Branch, Malang Regency. The context of the research in this study is "what are the factors that drive customer commitment in returning financing funds", to analyze the factors driving customer commitment in returning financing funds. This research was conducted in the period July-August 2020, using an interview system and field observations in the data collection process. The type of research used is a qualitative approach, both approaches with BMT institutions and with customers. The results of the study indicate that several factors encourage customer commitment in returning financing funds. Among them are internal factors which include, the amount of the loan, the value of the guarantee, the repayment period, and the chemistry between the institution and the customer. While external factors include income or business turnover, dependents of other parties, and family dependents.